INVENTARISASI TUMBUHAN BAWAH BERKHASIAT OBAT DI TAMAN NASIONAL GUNUNG GEDE PANGRANGO PROVINSI JAWA BARAT BERBASISKAN ANALISIS SPASIAL - Yanieta Arbiastutie; Djoko Marsono; Wahyuningsih MSH; Rishadi Purwanto (Universitas Tanjungpura, 2017)
Diversity of biological resources in primary forest is not only limited to the woody plant species, but also covered by underground plant which has diverse species high diversity. This underground plant as one part of the forest ecosystem is a plant that has potential as a medicine. The study aims to conduct an inventory of underground plant species in Gunung Gede Pangrango National Park West Java Province. The method for inventory used spasial analysis with land management unit and multi stage sampling. The spasial analysis used three categories, first the zonation map, second the soil characterization map and the third altitude map. The LMU consist of 6 areas with total plot number 60. The results showed there are 83 species underground plant consist of 45 family. The family consist of Acanthaceae, Annonaceae, Apiaceae, Apocynaceae, Araceae, Araliaceae, Aspleniaceae, Asteraceae, Balsaminaceae, Begoniaceae, Compositae, Convolvulaceae, Cucurbitaceae, Cyperaceae, Elaeagnaceae, Equisetaceae, Fabaceae, Gesneriaceae, Gramineae, Hypoxidaceae, Lamiaceae, Malvaceae, Marattiaceae, Melastomataceae, Menispermaceae, Moraceae, Musaceae, Myrsinaceae, Oxalidaceae, Passifloraceae, Piperaceae, Plantaginaceae, Polygalaceae, Primulaceae, Rosaceae, Rubiaceae, Sellagineaeeae, Smilaceae, Solanaceae, Symplocaceae, Urticaceae, Verbenaceae, Woodsiaceae, Zingiberaceae. The underground plant has a potential as medicinal plant.Keywords: Gunung Gede Pangrango National Park, inventory, land management unit, medicinal plant, underground plant